Impact of an infection control service in a university psychiatric hospital: significantly lowering healthcare-associated infections during 18 years of surveillance. Issue 2 (October 2020) - Büchler, A.C.; Sommerstein, R.; Dangel, M.; Tschudin-Sutter, S.; Vogel, M.; Widmer, A.F.
Summary: Background: Healthcare-associated infections (HAIs) lead to high morbidity and mortality. Data for HAIs in psychiatric hospitals are scarce, and are not derived from long-term surveillance. Aim: To assess the impact of an infection control service on the prevalence of HAIs in a psychiatric hospital over an 18-year period. Methods: In 1999, a professional infection control service was initiated at the University Psychiatric Hospital in Basel, Switzerland, with a part-time infection control nurse, a hospital epidemiologist, and administrative support. In addition to monitoring rates of multi-drug-resistant pathogens, eight prevalence studies using definitions outlined by the Centers for Disease Control and Prevention (CDC) were conducted between 2001 and 2018. For the primary outcome, a Poisson regression model was fitted to confirm cases of HAIs, standardized for patients at risk as a model offset. Findings: Overall, the predicted prevalence of nosocomial infections decreased from 3.7% (95% confidence interval (CI) 2.2–5.3%) in 2001 to 1.0% (95% CI 0.2–1.8%) in 2018 after introduction of an infection control service (incidence ratio rate (IRR) for yearly decrease of 0.93, 95% CI 0.87–0.98, P =0.007). Conclusions: Implementation of an infection control service may lead to a significant long-term decrease in HAIs, even in an institution caring for patients with low risk for HAIs, such as in psychiatric hospitals. In addition, epidemics and clusters were rapidly contained. Infection control services from acute-care hospitals should be expanded to psychiatric institutions, in order to decrease the incidence of HAIs and meet new challenges in times of emergence of multi-drug-resistant pathogens.